Fatal hepatitis B in infant born to a HBsAg carrier with HBeAb. Issue 3 (March 1985) - Ewing, C I; Davidson, D C
Abstract : Fulminant hepatic failure occurred in an 11 week old baby of a Caucasian mother who was hepatitis B surface antigen positive, B e antigen negative, and B e antibody positive. Infants of hepatitis B e antigen positive mothers receive immunoprophylaxis against hepatitis, unlike those born to mothers who are B e antibody positive.